Ventromedial Prefrontal Cortex Is Critical for Helping Others Who Are Suffering - Beadle, Janelle N.; Paradiso, Sergio; Tranel, Daniel (Frontiers in Neurology, 2018)
Neurological patients with damage to the ventromedial prefrontal cortex are reported to display reduced empathy towards others in their daily lives in clinical case studies. However, the empathic behavior of patients with damage to the ventromedial prefrontal cortex has not been measured experimentally in response to an empathy-eliciting event. This is important because characterizing the degree to which patients with damage to the ventromedial prefrontal cortex have lower empathic behavior will allow for the development of targeted interventions to improve patients’ social skills and in turn will help family members to better understand their impairments so they can provide appropriate supports. For the first time, we induced empathy using an ecologically-valid empathy induction in neurological patients with damage to the ventromedial prefrontal cortex and measured their empathic emotional responses and behavior in real time. Eight neurological patients with focal damage to the ventromedial prefrontal cortex were compared to demographically-matched brain-damaged and healthy comparison participants. Patients with damage to the ventromedial prefrontal cortex gave less money in the empathy condition to a person who was suffering (a confederate) than comparison participants. This provides the first direct experimental evidence that the ventromedial prefrontal cortex is critical for empathic behavior towards individuals who are suffering.